A Framework for Sustainable Eco-Friendly Product Development Based on TRIZ - Zainali, Nur Syaza; Ang, Mei Choo; Ng, Kok Weng; Ijab, Mohamad Taha (Advances in Visual Informatics, 2019)
Nowadays designers are facing challenges in designing sustainable eco-friendly products. Sustainable eco-friendly product design requires designers to conduct rigorous product research and have a development process that incorporates existing eco-efficiency elements. Sustainable eco-friendly product requirements are becoming more critical and are compulsory for all new product development in order to comply with the newly enacted environmental protection legislation. TRIZ consists of well-established tools utilized by many enterprises and has been successful in assisting designers in solving problems during new product development. However, TRIZ tools did not directly consider sustainable and environmentally friendly features in their recommended solutions for new product development. Hence, it is necessary to explore and investigate whether TRIZ can be adapted to assist designers to derive innovative and sustainable eco-friendly products. In this research work, we proposed an initial framework that links TRIZ Contradiction Matrix and eco-efficiency elements to assist designers in the development of sustainable eco-friendly products such as a lid fastener for food containers.